The role of Ge vacancies and Sb doping in GeTe: A Comparative Study of Thermoelectric Transport Properties in SbxGe1-1.5xTe and SbxGe1-xTe Compounds. (May 2022) - Chen, S.; Bai, H.; Wu, H.; Wu, J.; Chen, Z.; Su, X.; Uher, C.; Tang, X.
Abstract: Optimizing the thermoelectric properties of GeTe-based compounds usually involves the modulation of Ge vacancies and dopants. However, the mixture of vacancies and dopants makes the understanding of the doping mechanism complicated. Herein, two batches of Sbx Ge1-1.5x Te and Sbx Ge1-x Te compounds were prepared and the role of Ge vacancies and Sb were systematically studied. Alloying Sb2 Te3 in GeTe increases the concentration of cationic vacancies, which boosts the solubility limit of Sb in the GeTe compound. Moreover, such vacancies aggregate and form planar vacancies in Sbx Ge1-1.5x Te compounds. Both the cationic vacancies and Sb doping in the structure weaken the degree of the rhombohedral distortion. Additionally, doping with Sb in both cases lower the hole concentration effectively but with different regulation mechanism. Apart from the donor characteristic of Sb dopant in the Sbx Ge1-x Te compounds, the dissolution of Ge-precipitates facilitated by the additional Ge vacancies introduced via alloying with Sb2 Te3 reduces the carrier concentration. Furthermore, all-scale hierarchical architectures, including point defects, planar vacancies, and inherent grain boundaries, effectively scatter heat-carrying phonons, resulting in a low lattice thermal conductivity of 1.07 W m −1 K −1 for the Sb0.10 Ge0.85 Te compound. All these produce a peak ZT value of 1.85 at 724 K for the Sb0.10 Ge0.85 Te compound. Graphical abstract: Image 1 Highlights: Modulation of Sb content and cationic vacancies was carried out to optimize the thermoelectric performance of GeTe. The cationic vacancies aggregate and form planar vacancies in Sbx Ge1-1.5x Te compounds. Both the cationic vacancies and doping with Sb weaken the degree of the rhombohedral distortion. All-scale hierarchical architectures effectively scatter heat-carrying phonons in Sbx Ge1-1.5x Te compounds. Sb0.10 Ge0.85 Te compound achieves a maximum ZT value of 1.85 at 724 K.